Students’ Motivation in Learning English Through English Learning Videos Making - Rifqi Aulia Erlangga (Social Science Studies, 2021)
Video is a common media to use in teaching English in the past few years. English learning video can be an external factor that influence students’ motivation in studying English. English learning video that was designed by involving students as the actors predicted to have some common sense of belonging. Related to the purpose of the research, the result showed the students were motivated even more by learning English in a class using the video they are involved. Focusing on research methodology, descriptive quantitative research was applied to get the purpose of the research. The result in this study was represented in descriptive percentage.